PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPEJIGSAW TERHADAP PENINGKATAN MOTIVASI BELAJAR, KEMAMPUAN MEMORI SISWA DAN HASIL BELAJAR MATA PELAJARAN EKONOMI (STUDI KASUS PADA SMA WARGA SURAKARTA) - Dinna Riana; Baedhowi Baedhowi; Siswandari Siswandari (Universitas Sebelas Maret Surakarta, 2013)
Background: The learning model that applied on the economic subject in the WARGA High School of Surakarta nowadays much emphasizes on the conventional learning model, then the problems is the low of student learning motivation and memory capacity that has the effect on the bad result of student a chievement, that is just 47% of 155 social students in XI Grade of WARGA High School of Surakarta above the passing grade. By using the cooperative learning model of Jigsaw type, it is expected the result of student a chievement on economic subject matter will be improved. This research is aimed to know the influence of cooperative learning model of Jigsaw type on the increasing of student learning motivation, memory capacity and the result of student achievement on economic subject matter.Subjects and Methods: This research was a classroom action research that conducted in the two cycles and each cycle consisted of planning, implementation, monitoring and reflection. The subjects of research were 155 students of first semester in XI Grade of social class WARGA High School of Surakarta. The data sources were the student, venue and the phenomenon of learning process and documentation. The method of data collection were questionnaire, observation and interview. The validation of data was internal validation. The data analysis was qualitative analysis.Results: The result of research shows that before using the cooperative learning model of jigsaw type, the student learning motivation is just about 43.0, that means the number of students that achieve the passing grade are 15 students or 41.67% of classical completeness. In the I cycle the average score is increased becomes 53.4 with the number of students that achieve the passing grade are 23 students or 63.89% of the classical completeness. It is continued in the II cycle in which the decided target of the researcher is passed over by the average score is 56.0 by the classical completeness of 83.33%, that means 30 students of 36 have the high motivation. The beginning memory capacity of students is 50.08 by the classical completeness is 50.00%, those are 18 students. In the I cycle the score is improved to be 57.08 by the classical completeness is 69.44%, those are 25 students. In the II cycle, the score becomes 60 and the classical completeness is 80.56%, those are 29 students. The earlier result of study in the XI grade social class with the passing grade of 70.0 just has the score of 62 with the classical completeness of 44.00%. In the I cycle, the result of study gets the classical completeness of 63.0% with the average score is 73. In the II cycle, the target is overcome, in which the result is 80 with the classical completeness of 80.09%.